La responsabilidad del estudiante en un modelo pedagógico constructivista en programas de Ciencias de la Salud. - Caballero, Antonio Díaz; Hernández, Clara Vergara; Lorduy, Martha Carmona (Salud Uninorte)
Regarding pedagogy, conceptions are held world-wide about the role of an educator and a student during the learning process. Our concern is to pay close attention to our environment, where it is observed that the traditional pedagogy and content continues to dominate the subjects. Knowledge is vertically transmitted by the teacher to a group of students whose role is that of passive recipients, isolated and remote. the teacher is the holder of truth thanks to series of accumulated experience and what is transmitted, is the main part of the activity. Throughout this document, it is intended as a warning to teachers in the area and Piagetian approaches to the concept, who believes that knowledge is not just the recording of information, but that there should be mediation between a productive activity by the learner in interaction with the object, and that there are not innate cognitive structures in man. In contrast, this theory proposes that intelligence creates structures through the organization of successive actions performed on objects, so its constructivist psychogenesis is only based on a continuous developing of new operations and structures of thought. For the constructivist approach it is feasible, and it will require not only changes in the roles outlined for teachers and especially students, but in other areas of the education system.